Organizational Sociology: The Evolution of Thought from Classical to Modern Perspectives - Viola Febritiyasya; Wila Armanda; Ibnu Fajri; Akdila Bulanov (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article discusses an introduction to sociological organizations, classical organizations theory, and modern organizational theory. Organizational sociology is a branch of sociology that studies social relations, structures, and interactions within organizations. Classical organizational theory emphasizes the importance of structure, division of labor, efficiency, and rules in achieving organizational goals. Meanwhile, modern organizational theory views organizations as open systems that must adapt to environmental changes, technological developments, and social dynamics. This article uses a literature review method, collecting data from various relevant books and journals. The discussion shows that organizational development theory has evolved in line with changing times and the needs of organizations in facing environmental challenges. Therefore, organizations are required to be more flexible, innovative, and adaptable, to achieve their goals effectively and efficiently.